2003
DOI: 10.1007/s00221-003-1593-3
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia network mediates the control of movement amplitude

Abstract: This study addresses the hypothesis that the basal ganglia (BG) are involved speci®cally in the planning of movement amplitude (or covariates). Although often advanced, based on observations that Parkinson's disease (PD) patients exhibit hypokinesia in the absence of signi®cant directional errors, this hypothesis has been challenged by a recent alternative, that parkinsonian hypometria could be caused by dysfunction of on-line feedback loops. To re-evaluate this issue, we conducted two successive experiments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 111 publications
6
44
0
1
Order By: Relevance
“…In contrast, Krakauer et al (2004) found that adaptations to changes in visuomotor gain induced only a subtle increase in rCBF signal in a subset of subcortical motor areas activated in their control task (left insula/putamen, left medial cerebellum, and right putamen) and no significant activation outside of the regions active during the control task. These results are consistent with the proposed role of basal ganglia in scaling the magnitude and rate of increase of muscle activity during movement (Horak and Anderson 1984) and thus in controlling movement extent and velocity (Anderson and Horak 1985;Desmurget et al 2003Desmurget et al , 2004Mazzoni et al 2007;Turner and Anderson 1997;Turner et al 2003). Indeed, inactivation of basal ganglia output pathways in animal models reduces the extent of goal-directed movements but alters neither reaction times (Mink and Thach 1991) nor the normal activation sequence seen during reaching prior to inactivation (Horak and Anderson 1984).…”
Section: Separate Neural Substrates Encoding Movement Direction and Esupporting
confidence: 85%
“…In contrast, Krakauer et al (2004) found that adaptations to changes in visuomotor gain induced only a subtle increase in rCBF signal in a subset of subcortical motor areas activated in their control task (left insula/putamen, left medial cerebellum, and right putamen) and no significant activation outside of the regions active during the control task. These results are consistent with the proposed role of basal ganglia in scaling the magnitude and rate of increase of muscle activity during movement (Horak and Anderson 1984) and thus in controlling movement extent and velocity (Anderson and Horak 1985;Desmurget et al 2003Desmurget et al , 2004Mazzoni et al 2007;Turner and Anderson 1997;Turner et al 2003). Indeed, inactivation of basal ganglia output pathways in animal models reduces the extent of goal-directed movements but alters neither reaction times (Mink and Thach 1991) nor the normal activation sequence seen during reaching prior to inactivation (Horak and Anderson 1984).…”
Section: Separate Neural Substrates Encoding Movement Direction and Esupporting
confidence: 85%
“…These new results, which are in agreement with the findings reported by other authors on the role of basal ganglia in the control of movement amplitude in patients affected by Parkinson disease (Desmurget et al, 2003), demonstrate the prospective usefulness of NME. However, a thorough interpretation of these findings would go beyond the scope of this article and will not be discussed here, but it is worth mentioning that, at a theoretical level, conjoint analysis approaches can lead to interesting results that might deepen our understanding of the neural correlates of specific features of coordination, such as those reported in a recent paper by the authors on the neural correlates of intention during bimanual coordination and switching between patterns of different stability (De Luca et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…39,132 Plasticity also implies changes in activity within the 'non-primary' structures of the sensorimotor network, 133 such as the supplementary motor area and lateral premotor cortex, 134 cingulum, 135 insula, posterior parietal cortex, 136 cerebellum, 137 deep grey nuclei and thalamus. 138 Plasticity equally implies changes in the effective connectivity within the whole functional network 139 -as revealed by measuring the coherence of the activity between the distinct areas involved in sensorimotor function. 140 Concerning language and cognition, the current view is of a spatio-temporal functioning of parallel distributed cortico-cortical and cortico-subcortical networks, [141][142][143] with both simultaneous and successive participation of mosaics of hierarchically organized areas, some of them being essential while others being compensable -with an interindividual variability.…”
Section: Natural Plasticity In Humansmentioning
confidence: 99%